(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research uses a descripttive quantitative method. Sources of research data, observation, interviews, questionnaires, and literature study. The research sample consisted of 40 employees, the sampling was saturated sampling. It is known that the results of the t (partial) work motivation show that if work motivation is maximized, employee performance will also increase. The results of the t-test (partial) of work ability show that if the work ability is improved, the employee’s performance will also increase. Meanwhile, the results of the F test (simultaneous) show that the independent variable has an influence on the dependent variable. The coefficient of determination test results showed that work motivation and work ability contributed 51% to employee performance. Meanwhile, the remaining 49% is explained by other variables which have not been researched. The results of the descriptive analysis show that the largest proportion of employee performance is in the high enough category, while for work motivation and work ability the largest proportion is in the medium category. The results of this study concluded that it is very important for companies to manage their employees as well as possible so that their performance increases.